Efeito do revestimento de fécula de mandioca na conservação pós-colheita da banana - Souza, Álesson Antônio Silva de (Brasil, 2024)
Postharvest technologies to extend the shelf life of fruits have gained prominence in recent years, due to the growing demand for fruits with sensory and visual quality. Edible polymer-based coatings are gaining strength in the market because they are low cost and present promising results, especially for tropical fruits. Banana (Musa spp.), one of the most consumed fruits in the world, faces difficulties with export due to poor postharvest quality. This study aimed to evaluate the effect of edible coating based on cassava starch on the postharvest conservation of bananas. The experiment was conducted in a randomized block design in a 3 x 4 factorial arrangement (three treatments, namely: fruits without coating (control), with 4% cassava starch and 8% cassava starch in 4 storage periods: 3, 6, 9 and 12 days). The physical (weight loss and firmness) and physicochemical (titratable acidity (TA), pH, soluble solids (SS) and SS/TA ratio) characteristics were evaluated over 12 days. The results indicate that the cassava starch treatments were effective in reducing weight loss, preserving fruit firmness, with the 8% concentration being the most effective in maintaining the physicochemical characteristics. It is concluded that the edible cassava starch coating represents a sustainable alternative to extend the shelf life of bananas (Musa spp.) and reduce post-harvest losses.